Culinary Heritage as Tourist Attraction in Kota Tua, Padang-West Sumatera - Melati Sekar Sari; I Gusti Ngurah Widyatmaja; I Putu Sucita Yanthy (Asian Journal of Social and Humanities, 2023)
This research examines the culinary heritage in the Kota Tua area as one of the Integrated Tourism Areas in Padang City. This area is enriched with historical buildings and culinary influenced by various ethnicities that have been around for decades. However, culinary tourism development in this area is relatively slow because of a lack of active collaboration between stakeholders. This research aims to analyze the potential and obstacles to developing culinary heritage as a tourist attraction in the Kota Tua of Padang. This study used a descriptive qualitative method. The data collection technique used was in-depth interviews with stakeholders. The data taken was processed and analyzed using thematic analysis techniques. The results of this research show the importance of an effective development of culinary tourism as a tourist attraction in Kota Tua, Padang. In developing this area as a tourist attraction, it is formulated from thematic elements of stakeholder statements during interviews. These elements indicate development strategies in accordance with the potential and obstacles experienced during the process of developing culinary tourism as a tourist attraction. In an effort to overcome the issue of developing culinary tourism as a tourist attraction in Kota Tua, Padang requires the holistic involvement of relevant stakeholders in producing regional development through historical narratives regarding culinary products and storytelling as well as events such as the Culinary Tourism Festival.